2016
DOI: 10.3390/healthcare4030048
|View full text |Cite
|
Sign up to set email alerts
|

Illustrating the Multi-Faceted Dimensions of Group Therapy and Support for Cancer Patients

Abstract: In cancer support groups, choice of therapy model, leadership style, and format can impact patients’ experiences and outcomes. Methodologies that illustrate the complexity of patients’ group experiences might aid in choosing group style, or testing therapeutic mechanisms. We used this naturalistic study as a beginning step to explore methods for comparing cancer group contexts by first modifying a group-experience survey to be cancer-specific (Group Experience Questionnaire (GEQ)). Hypothesizing that therapist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…However, a constraint of this research is that our sample mostly included Caucasian women while support-seeking literature suggests differences among individuals from different cultural backgrounds. 20, 21 Additionally, while different models of support exist utilizing various therapeutic and leadership styles, formatting, setting and components, all of which may impact patient benefit, 3, 22 we focused singularly on professionally-run support groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a constraint of this research is that our sample mostly included Caucasian women while support-seeking literature suggests differences among individuals from different cultural backgrounds. 20, 21 Additionally, while different models of support exist utilizing various therapeutic and leadership styles, formatting, setting and components, all of which may impact patient benefit, 3, 22 we focused singularly on professionally-run support groups.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding when support groups are presented, support resources should be addressed at every interaction with an oncology provider because cancer survivors’ needs shift and change throughout a cancer journey. 22 It has been over ten years since the Institute of Medicine published a landmark call for attention to the transition from primary to posttreatment cancer care 11 with ongoing appeal from the scientific community for special consideration to the transition to posttreatment. 26 Starting an anti-hormonal treatment and transitioning to posttreatment care presents an especially good time to remind the patient of the match between professionally-led support groups and a patient’s evolving support needs.…”
Section: Discussionmentioning
confidence: 99%
“…Group processes are the active ingredients in group psychotherapy 15 and were measured using group cohesion 16 and valued group experiences. 17 Changes in group cohesion were measured using the Group Cohesiveness Scale 18 (GCS; completed at weeks 1, 4, 7, and 9 across the 10-week intervention). Participants rated the cancer support group experiences they valued most by completing the Group Experience Questionnaire (GEQ; subscales: expressing true feelings, developing a new attitude, accessing information and advice, establishing supportive contact, and discussing sexual concerns) postintervention.…”
Section: Methodsmentioning
confidence: 99%
“…The CCK intervention has the potential to close the gap between cancer survivors and the general population in health-related quality of life and mental health directly through learning coping strategies to reduce stress and indirectly through improving diet quality [ 70 ]. Furthermore, in a naturalistic study, Giese-Davis et al showed that CSC therapist-led support groups provided an experience in which the development of a new attitude was valued [ 71 ].…”
Section: Discussionmentioning
confidence: 99%